A phenomenological study exploring the challenges of establishing an effective hospitality work based learning program at UiTM / Khairil Anuar Bahari ... [et al.] - Bahari, Khairil Anuar; Mohd Saber, Joesri; Ibrahim, Mohd Zool Fadli; Raja Mustapha, Raja Iskandar Putera; Johari, Noorsa Riza (Universiti Teknologi MARA, Perlis, 2025)
This phenomenological study explores the complexities involved in establishing a successful hospitality internship program at Universiti Teknologi MARA (UiTM). The research utilizes the Experiential Learning Theory as a framework to examine the experiences of seven work base learning (WBL) coordinators from UiTM and employing interviews with semi-structured questions and thematic investigation as the primary methodologies. The study extensively identifies and analyzes key themes, including behavior, restriction, diversion, placement, sexual misconduct, expectation, and student readiness. Through comprehensive exploration, the findings highlight the complex challenges confronted by work base learning coordinators in ensuring the effectiveness of WBL programs within the hospitality sector. It emphasizes the crucial need to address these challenges to elevate the quality and efficacy of hospitality WBL programs at UiTM. The study's findings are expected to offer valuable guidance for all relevant stakeholders, aiding in the enhancement of WBL program design and strategies, particularly within the hospitality business. Moreover, it is expected to offer students and coordinators with essential insights which allowing them to effectively prepare for and address the challenges associated with coordinating and participating in the internship procedure.